An exploratory inquiry of healthcare students’ practicum experience with a digital critical reflection tool - Huynh , Tan (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This pilot qualitative research aims at exploring the effects of an App designed by Birmingham City University on healthcare students’ critical reflection levels. Ten healthcare students from Nguyen Tat Thanh University took pictures and videos using the App and critically reflected on them in comparison with their classroom experience. The results show that the App promotes the subjects’ critical evaluation of their experience.